IFRS Influence on Financial Reporting Quality - Miková, Tereza; Zárybnická Žárová, Marcela, 1959-; Mejzlík, Ladislav, 1961-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
Dissertation interfaces two current accounting issues: International Financial Reporting Standards and financial reporting quality. Theoretical framework begins with historical development and contemporary position of IFRS. It is followed by financial accounting quality where overview of methods is used for assessment of accounting quality. The literature underpinning represents the final part of theoretical part. Dissertation examines publicly traded Czech companies on Prague stock exchange and together their financial statements are presented under Czech accounting standards and later on switched on International Financial Reporting Standards. Final sample consists of 15 companies (222 firm-year observations) during period 1993-2013. World accepted models were adjusted before its application to be more convenient for Czech environment. Research results show that there are only limited improvements in financial reporting quality in IFRS period, only some companies are models applicable and therefore law and professional environment play significant role within quantitative methods.
Vedoucí práce: Marcela Žárová
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations